The NAC transcription factor MdNAC29 negatively regulates drought tolerance in apple - Li, Sen; Jing, Xiuli; Tan, Qiuping; Wen, Binbin; Fu, Xiling; Li, Dongmei; Chen, Xiude; Xiao, Wei; Li, Ling (Frontiers in Plant Science, 2023)
Drought stress is an adverse stimulus that affects agricultural production worldwide. NAC transcription factors are not only commonly involved in plant development and growth, but also play different roles in abiotic stress response. Here, we isolated the apple MdNAC29 gene, and its role in regulating drought stress was investigated. Subcellular localization experiments showed that MdNAC29 was localized to the nucleus and the transcription level was induced by drought treatment. Over-expression of MdNAC29 reduced drought tolerance in apple plants, calli and tobacco, and exhibited higher relative conductivity, malondialdehyde (MDA) content and lower Chlorophyll content under drought stress. The transcriptomic analyses and qRT-PCR results of MdNAC29 transgenic apple showed that MdNAC29 might reduce drought resistance by modulating the expression of photosynthesis and leaf senescence related genes. Yeast one-Hybrid (Y1H) and Dual-Luciferase (LUC) assays demonstrated that MdNAC29 directly repressed the expression of MdDREB2A. Moreover, Yeast Two-Hybrid (Y2H) assays and Bimolecular Fluorescence Complementation (BiFC) assays demonstrated that MdNAC29 interacted with the F-box protein PP2-B10-like (MdPP2-B10), which is responded to drought stress. Taken together, our results indicate that MdNAC29 plays a negative regulator in the drought resistance, which can provide theoretical basis for further molecular mechanism research.